2015
DOI: 10.4049/jimmunol.1401108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of System Xc− Transporter Attenuates Autoimmune Inflammatory Demyelination

Abstract: T cell infiltration into the central nervous system (CNS) is a significant underlying pathogenesis in autoimmune inflammatory demyelinating diseases. Several lines of evidence suggest that glutamate dysregulation in the CNS is an important consequence of immune cell infiltration in neuroinflammatory demyelinating diseases; yet, the causal link between inflammation and glutamate dysregulation is not well understood. A major source of glutamate release during oxidative stress is the system xc− transporter, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 72 publications
7
85
2
2
Order By: Relevance
“…The in vivo relevance of cystine uptake for T cell function was studied by Evonuk et al (Evonuk et al, 2015). These studies demonstrated that autoreactive T cells in experimental autoimmune encephalomyelitis (EAE) require cystine uptake for their function as pharmacological blockade or genetic deletion of xCT prevented EAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo relevance of cystine uptake for T cell function was studied by Evonuk et al (Evonuk et al, 2015). These studies demonstrated that autoreactive T cells in experimental autoimmune encephalomyelitis (EAE) require cystine uptake for their function as pharmacological blockade or genetic deletion of xCT prevented EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Cystine uptake is required for T cell activation (Srivastava et al, 2010) and activated T cells require extracellular cystine for proliferation (Levring et al, 2012) and DNA synthesis (Levring et al, 2015). Autoreactive T cells depend on cystine uptake as pharmacologic blockade attenuates experimental autoimmune encephalomyelitis (EAE) and Slc7a11-deficient mice are protected from EAE (Evonuk et al, 2015). Interestingly, myeloid derived suppressor cells (MDSC) are proposed to block T cells in part by depleting extracellular cystine that impairs anti -tumor T cell response (Srivastava et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to astrocytes, increases in inflammatory cytokines such as TNF and IL-1β are known to impair glutamate buffering and clearance by oligodendrocyte EAATs, and trigger glutamate toxicity (Takahashi et al, 2003a;Takahashi et al, 2003b). Indeed, inhibition of the expression and functioning of glutamate transporters such as EAATs and xC-transporters in axonal tracts is sufficient to induce oligodendrocyte loss and demyelination, which undermines brain connectivity (Domercq et al, 2007;Evonuk et al, 2015).…”
Section: Oligodendrocytes and Glutamatementioning
confidence: 99%
“…In C3H/HeSnJSlc7a11 sut/sut (sut/sut) mice that are deficient for system x c − , proteolipid protein (PLP)-induced EAE was attenuated compared to their wild type littermates. The latter effect could be replicated by pharmacological inhibition of system x c − with sulfasalazine (SAS) and (S)-4-carboxyphenylglycine [43]. Whereas the above-described studies suggest that enhancement of system x c − contributes to the pathogenesis of MS, a recent report of Morales Pantoja et al showed diminished xCT mRNA and protein levels in the mouse spinal cord during the course of myelin oligodendrocyte glycoprotein (MOG) 35–55 peptide-induced EAE [44].…”
Section: Introductionmentioning
confidence: 99%